Coma morphology and dust emission pattern of comet C/2020 F3 (NEOWISE). Issue 4 (30th June 2021) - Manzini, F; Oldani, V; Ochner, P; Barbotin, E; Bedin, L R; Behrend, R; Fardelli, G
ABSTRACT: The recent close approach of comet C/2020 F3 (NEOWISE) allowed us to study the morphology of its inner coma. From the measurement of the dust ejection velocity on spiral structures expanding around the nucleus, we estimated a mean deprojected expansion velocity V d  = 1.11 ± 0.08 km s −1 . Assuming that a new shell formed after every rotation of the comet, a period of 7.8 ± 0.2 h was derived. The spin axis orientation was estimated at RA 210° ± 10°, Dec.  +35° ± 10°. The coma morphology appears related to two strong, diametrically opposite emissions located at mid-latitudes on the nucleus. A qualitative modelling of the coma produced consistent results with a wide range of dust sizes (0.80–800 μm), with inversely correlated densities (0.003–3.0 g cm −3 ). Images taken with Vj and r -Sloan filters showed a greater concentration of dust in the first two shells, and an increasing density of radicals emitting in the B and V band passes from the third shell outwards. Striae-like structures in the tail suggest that dust particles have different sizes.